Pelatihan Pembuatan Instalasi Hidroponik bagi Mahasiswa Biologi melalui Program Ppupik di Laboratorium Kebun Percobaan Biologi FMIPA UNM - Adnan, Adnan; Kurnia, Nani; Faisal, Faisal; Saleh, Andi Rahmat; Saparuddin, Saparuddin (Jurnal Abdi Negeriku, 2022)
Not only issuing alumni who have qualified knowledge, producing young entrepreneurs is also one of the roles of a university. One of the programs held to support this achievement is the implementation of the Campus Intellectual Product Business Development Program or PPUPIK. Through PPUPIK, student creativity will also develop optimally. One of the PPUPIK activities that was developed in the Biological Experimental Garden Laboratory (LKPB) FMIPA UNM in 2019 was hydroponic development training for students. The hydroponic system is a cultivation system using water that contains nutrients and minerals without soil. Hydroponics training was held for one semester at the Biology Experimental Garden, FMIPA UNM, attended by 20 students. The types of hydroponics that were trained included (1) simple hydroponics from Styrofoam, (2) Nutrient Film Technique (NFT), (3) EBB and Flow Technique (EFT), and (4) Deep Flow Technique (DFT). The training was carried out using a number of methods, namely interviews, focus group discussions (FGD), demonstrations, and work practices. From this hydroponic training, 11 types of hydroponic installations were produced that can be developed by students to later be used in entrepreneurship activities in related fields.